Effect of calcined nanoclay on microstructural and mechanical properties of chemically treated hemp fabric-reinforced cement nanocomposites - Hakamy, Ahmad Magbul M; Shaikh, Faiz; Low, It Meng (ELSEVIER, 2015)
The influence of calcined nanoclay (CNC) and chemical treatment on the microstructure and mechanical properties of treated hemp fabric-reinforced cement nanocomposites has been investigated. The optimum hemp fabric content for these nanocomposites is 6.9 wt% (i.e. 6 fabric layers). Alkali-treated hemp fabric-reinforced cement composites exhibit the highest flexural strength when compared to their non-treated counterparts. In addition, mechanical properties are improved as a result of CNC addition. An optimum replacement of ordinary Portland cement with 1 wt% CNC is observed through reduced porosity and increased density, flexural strength and fracture toughness in treated hemp fabric-reinforced nanocomposite. It is shown that CNC behaves not only as a filler to improve the microstructure, but also as the activator to facilitate the pozzolanic reaction and thus improved the adhesion between the treated hemp fabric and the matrix.